Atsaru Ta’lῑmi ‘Ilmi Al-Lughati Al- āli Nahwi Dawāfi’i Al-Thalabati Fi Ta’lῑmi Al-Lughati Al-‘Arabiyyati - Azisi; Syafitri, Ria; Nurfaiza; Mohd Shauki Bik Bin Mohd Kasim (Lughawiyyat: Jurnal Pendidikan Bahasa dan Sastra Arab, 2022)
The background of this research is related to the motivation to learn Arabic in students using information technology. This aims to identify the impact of IT-based Arabic language learning on stimulating student learning. In this study, the researchers used quantitative methods, and this type of research is field research. Observational data collection methods, questionnaires and documentaries use data analysis using product torque codes. The results of this study are divided into two parts, namely the main findings and the sub-results. The main finding was that there was an effect of automated language teaching on students' motivation in teaching Arabic, but the effect was low, the known arithmetic r (0.3301) was greater than rtabular (0.2311) of the sum n = 80, db = n - nr = 78, (α) = 5%. This indicates that the null hypothesis (H0) is returned and the hypothesis of option (H1) is acceptable.  The secondary outcomes are: a) the effect of automated language teaching on students' internal motivation in teaching Arabic is low, arithmetic r (0.2647) is greater than rtabular (0.2311) of the sum n = 80, db = n-nr = 78, (α) = 5%. This indicates that the null hypothesis (H0) is returned and the hypothesis of option (H1) is acceptable. b) The effect of automated language teaching on the external motivation of students in teaching Arabic is also low, it is known that the calculation r (0.2359) is greater than rtabular (0.2311) of the sum n = 80, db = n - nr = 78, (α) = 5%. This indicates that the null hypothesis (H0) is returned and the hypothesis of option (H1) is acceptable.